La izquierda populista iberoamerican como séptima generación de las izquierdas políticamente definidas según la teoría de las izquierdas del materialismo filosófico - Armesilla Conde, Santiago Javier (Nómadas. Critical Journal of Social and Juridical Science, 2015)
In this article we explores the Iberoamerican (latin american or, at least, in its roots and core) populist left-wing phenomenon as the latest politically defined left-wing generation from the coordinates of the political and philosophical materialism on the basis of the basic features of its theory of the left-wing generation: the universalistic rationalism, the revolutionary rationalization by holizacion, the revolutionary subject and the definition with respect to the State, studying at the same time the shaping of populism, its expansion beyond Latin America and its possible future on the basis of its fundamental bases.